Ultrasound imaging in spinal cord injury patients with shoulder pain - Jittima Saengsuwan; Patpiya Sirasaporn (Journal of Orthopaedics, Trauma and Rehabilitation)
Objective To examine shoulder ultrasound imaging in both tetraplegic and paraplegic spinal cord injury (SCI) patients with shoulder pain. Methods All 28 individuals with SCI with shoulder pain were enrolled in this study. Fifty-six shoulders were evaluated by ultrasound (US) imaging. Results Fourteen tetraplegics and 14 paraplegics were enrolled (age 45.4 ± 13.8 years [mean ± SD]). Median time post-SCI was 8.6 years. Twenty-three individuals (82.1%) were independent in transfer and four individuals (14.3%) were partially independent in transfer. The prevalence of shoulder pain was 78.6% in manual wheelchair ambulators, 10.7% in gait aids users, 7.1% in wheelchair sitters, and 3.6% in no assistive device individuals. Abnormal US imaging was found in 24/28 (85.7%) individuals. Total shoulder US abnormalities were 38 units. Most common abnormal US imaging was supraspinatous tendinosis (42.1%), biceps tendon effusion (23.7%), positive dynamic supraspinatus impingement (21.1%), and subdeltoid bursitis (18.4%). Conclusions Shoulder ultrasonographic abnormalities were common in the patients with SCI with shoulder pain. The supraspinatus tendinosis is the most common abnormal US imaging in patients with SCI with shoulder pain.